Glass-resin composite
The glass resin composite, with a thickness of 800 μm or less and specific resin layer configurations, addresses the challenge of cracking during the roll-to-roll process by ensuring a 10% or less probability of cracking when bent with a defined radius of curvature, thus enhancing the composite's durability and processability.
Patent Information
- Application Number
- JP2023166771
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing glass resin composites face challenges in suppressing the occurrence of cracks in the effective area of the glass surface when subjected to the roll-to-roll process, particularly during cutting and attachment to a flexible film substrate.
A glass resin composite with one or more resin layers on at least one surface of the glass sheet, where the thickness is 800 μm or less, and the probability of cracking is 10% or less when bent with a specific radius of curvature, as defined by the formula involving the inner radius of curvature, number of layers, Young's modulus, and thickness of the resin layers.
The solution effectively suppresses cracking in the effective area of the glass surface during the roll-to-roll process, improving the yield of glass resin composites wound with a film substrate.
Smart Images

Figure 2025057104000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass resin composite. [Background technology]
[0002] Glass resin laminates in which a resin layer is laminated on extremely thin, flexible thin glass (hereinafter also referred to as "glass sheet") are used in image display devices such as liquid crystal display elements and organic EL elements, semiconductor elements, solar cells, etc. The glass sheet used in the glass resin laminates is flexible and can be wound into a roll, so that the glass sheet in roll form can be unwound using a roll-to-roll process, processed such as laminating a resin layer or printing, and then wound into a roll again to produce the glass resin laminate.
[0003] As a method for producing a glass resin laminate using a roll-to-roll process, for example, a method has been disclosed in which a roll-to-roll laminating device is used to laminate a flexible glass layer to other material sheets including a PVA layer and a TAC layer in a polarizer structure to form a laminate roll (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] U.S. Patent No. 8,525,405 Summary of the Invention [Problem to be solved by the invention]
[0005] However, Patent Document 1 does not disclose how to prevent the occurrence of cracks within the effective area of the surface of the flexible glass layer when the laminate roll is cut or otherwise formed into chips, and then the chipped laminate roll is attached to a flexible film substrate wound into a roll and transported using a roll-to-roll process.
[0006] When a glass resin composite chipped from a glass resin laminate is attached to a rolled film substrate via an adhesive or the like, and then transported as a web (web handling) using a roll-to-roll process and wound up into a roll, there is a problem in that cracks may occur in the effective area of the surface of the glass sheet.
[0007] From the viewpoint of improving the yield of the glass resin composite wound into a roll on a film substrate, it is important that the glass resin composite can be wound into a roll without causing cracks in the effective area of the surface of the glass sheet.
[0008] An object of one aspect of the present invention is to provide a glass resin composite that can suppress the occurrence of cracks in an effective area of the glass surface even when a roll-to-roll process is used. [Means for solving the problem]
[0009] One aspect of the present invention is A glass resin composite having one or more resin layers on at least one surface of a glass sheet, The thickness of the glass resin composite is 800 μm or less, The glass resin composite has a probability of 10% or less when the glass resin composite is bent toward one surface of the glass resin composite with a curvature radius that satisfies the following formula (1):
number
[0010] One aspect of the present invention can suppress the occurrence of cracks in an effective area of the glass surface even when using a roll-to-roll process. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic cross-sectional view showing a configuration of a glass resin composite according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing an example of a method for winding up a glass resin composite using a roll-to-roll transport device. [Diagram 3] FIG. 11 is a schematic cross-sectional view showing an example of another configuration of the glass resin composite. [Figure 4] FIG. 11 is a schematic cross-sectional view showing an example of another configuration of the glass resin composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail. In order to facilitate understanding of the description, the same components in each drawing are given the same reference numerals, and duplicated descriptions will be omitted. In addition, the scale of each member in the drawings may differ from the actual scale. In this specification, "~" indicating a numerical range means that the numerical values before and after it are included as the lower and upper limits, unless otherwise specified.
[0013] <Glass resin composite> A glass resin composite according to an embodiment of the present invention will be described. Fig. 1 is a schematic cross-sectional view showing the configuration of a glass resin composite according to this embodiment. As shown in Fig. 1, a glass resin composite 1 according to this embodiment includes a glass sheet 10 and a multilayer resin layer 20 arranged on one main surface (lower surface) 10a of the glass sheet 10. The glass resin composite 1 has a substantially rectangular shape in a plan view, and is attached to one main surface of a rolled flexible film substrate via an adhesive or the like using a roll-to-roll process, and then wound into a roll.
[0014] 1 uses a three-dimensional Cartesian coordinate system with three axial directions (X-axis, Y-axis, and Z-axis), with the width direction of the glass sheet 10 defined as the X-axis, the length direction defined as the Y-axis, and the thickness direction defined as the Z-axis. The direction from the multilayer resin layer 20 of the glass sheet 10 toward the glass sheet 10 (outside) is defined as the +Z-axis direction, and the opposite direction (inside) is defined as the -Z-axis direction. In the following description, the +Z-axis direction may be referred to as up or upward, and the -Z-axis direction may be referred to as down or downward.
[0015] When the glass resin composite 1 is bent on one of its surfaces, the lower surface 1a (the surface on the multilayer resin layer 20 side), with a curvature radius that satisfies the following formula (1) so that the glass sheet 10 is convex, the probability of cracking occurring in the glass sheet 10 is 10% or less, preferably 9.0% or less, more preferably 5.0% or less, and even more preferably 3.0% or less.
[0016]
number
[0017] In formula (1), R0 is the inner radius of curvature of the glass resin composite [mm], i and k are integers, l is the number of layers [layers] including the resin layer and the glass sheet when counting from the inside of the resin glass laminate to the glass sheet, n is the total number of layers [layers], and E i is the Young's modulus of the i-th layer [MPa], and t i is the thickness [μm] of the i-th resin layer, and t0 is 0.
[0018] In addition, the Young's modulus E of the resin layer in formula (1) i can be measured by the resonance method based on JIS R 1602 (measurement temperature: 25°C) or using an autograph under the following Young's modulus measurement conditions. -Young's modulus measurement conditions- ·Measurement temperature: 25℃ Sample size: thickness 50μm, width 2cm, length 15cm Distance between chucks: 10cm Pulling speed: 10mm / min
[0019] The radius of curvature R0 in formula (1) means the radius of an imaginary circle with which the glass resin composite 1 is in contact. As described above, the glass resin composite 1 is wound up by a roll-to-roll process, and therefore the radius of curvature in formula (1) is preferably the radius of a roll with which the glass resin composite 1 is in contact. If the radius of curvature in formula (1) is the radius of a roll, it is possible to confirm the occurrence rate of cracks in the glass sheet 10 when the glass resin composite 1 is wound around a roll having a radius of curvature that satisfies the above formula (1).
[0020] The thickness of the glass resin composite 1 is 800 μm or less, preferably 700 μm or less, more preferably 400 μm or less, and further preferably 350 μm or less.
[0021] In this specification, the thickness of the glass resin composite 1 refers to the length in a direction perpendicular to the main surface of the glass resin composite 1. The thickness of the glass resin composite 1 may be, for example, the thickness measured at an arbitrary location on the cross section of the glass resin composite 1, or may be the average value of the measured values measured at several arbitrary locations. Hereinafter, the definition of thickness is similarly applied to other members.
[0022] When the other surface of the glass resin composite 1, that is, the upper surface 1b (the surface on the glass sheet 10 side), is bent with a radius of curvature that satisfies the above formula (1), the probability of cracks occurring in the glass sheet 10 is preferably 10% or less, more preferably 5.0% or less, and even more preferably 3.0% or less.
[0023] [Glass sheet] The glass sheet 10 has a plate-like (sheet-like) shape and is substantially rectangular in plan view. The width and length of the glass sheet 10 may be any appropriate size.
[0024] The glass sheet 10 is formed using a long glass ribbon. The glass sheet 10 is obtained by cutting the long glass ribbon. Note that the term "long" means an elongated shape having a sufficiently long length relative to its width, and includes, for example, an elongated rectangular shape having a length 10 times or more, preferably 20 times or more, relative to its width.
[0025] The glass sheet 10 can be formed using any suitable glass material. The glass material constituting the glass sheet 10 is preferably inorganic glass. Inorganic glass can be classified according to composition, such as soda-lime glass, borate glass, aluminosilicate glass, and quartz glass, and can be classified according to alkali components, such as non-alkali glass and low-alkali glass. The content of alkali metal components (e.g., Na2O, K2, Li2O) in the above glass is preferably 15 mass % or less, and more preferably 10 mass % or less.
[0026] The thickness of the glass sheet 10 is preferably 20% to 75%, more preferably 25% to 71%, and even more preferably 28% to 65% of the thickness of the glass resin composite 1. When the thickness of the glass sheet 10 relative to the glass resin composite 1 is within the above-mentioned preferred range, the glass sheet 10 becomes easier to bend, and the glass resin composite 1 becomes easier to wind up in a roll-to-roll process. Furthermore, even if a crack occurs on an edge surface of the glass sheet 10, the multilayer resin layer 20 makes it easier to prevent the crack from progressing to the center of the main surface of the glass sheet 10.
[0027] The thickness of the glass sheet 10 can be appropriately designed according to the thickness of the glass resin composite 1, and is preferably, for example, 30 μm to 300 μm. The thickness of the glass sheet is more preferably 35 μm or more, and further preferably 40 μm or more. The thickness of the glass sheet is more preferably 250 μm or less, and further preferably 230 μm or less. When the thickness of the glass sheet 10 is within the above preferred range, the glass sheet 10 becomes easy to bend, and the glass resin composite 1 becomes easy to wind up in a roll-to-roll process.
[0028] The length and width of the glass sheet 10 are not particularly limited and can be appropriately designed depending on the size of the glass resin composite 1, and are, for example, preferably 50 mm to 5000 mm, and more preferably 100 mm to 1500 mm. The length and width of the glass sheets 10 may be the same or different.
[0029] The glass sheet 10 is preferably transparent. Here, transparency means that the glass sheet 10 has light transmittance that transmits visible light (light with a wavelength of 380 nm to 780 nm) through the inside of the glass sheet 10 when the visible light is irradiated from the outside of the glass sheet 10, and the visible light transmittance of the glass sheet 10 is preferably 85% or more. The light transmittance is measured using "Plastics - Determination of total light transmittance and total light reflectance" as specified in JIS K 7375:2008.
[0030] The refractive index of the glass sheet 10 at a wavelength of 550 nm may be in the range of 1.4 to 1.65.
[0031] The density of the glass sheet 10 is not particularly limited and is, for example, 2.3 g / cm 3 ~3.0g / cm 3 It is acceptable to do so.
[0032] The method for manufacturing the glass sheet 10 is not particularly limited, and a general manufacturing method may be used. The glass sheet 10 is manufactured, for example, by melting a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon at a temperature of 1400°C to 1600°C, forming it into a thin plate, and then cooling it. The glass sheet 10 may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to increase its smoothness.
[0033] The glass sheet 10 may be formed by a general method. For example, the slot downdraw method, the fusion method, the float method, etc. may be used as the method for forming the glass sheet 10. Among these, when the fusion method is used, the surface of the glass sheet is not contaminated with tin or the like as in the case of the float method, so there is no need to perform a polishing process, and it is easy to ensure the smoothness and thinness of the surface. Therefore, from these viewpoints, it is preferable to use the fusion method.
[0034] A commercially available glass sheet may be used as it is as the glass sheet 10, or a commercially available glass sheet may be polished to a desired thickness before use. Examples of commercially available glass sheets include "7059", "1737" and "EAGLE2000" manufactured by Corning Incorporated, "AN100" manufactured by Asahi Glass Co., Ltd., "NA-35" manufactured by NH Techno Glass Co., Ltd., "OA-10" manufactured by Nippon Electric Glass Co., Ltd., and "D263" or "AF45" manufactured by Schott Co., Ltd.
[0035] [Multi-layer resin layer] 1, the multilayer resin layer 20 is a layer made of resin, and includes one or more resin layers 21N (N is an integer of 1 or more) stacked together. The N resin layers 21N are stacked downward from the lower surface 10a side of the glass sheet 10 in the order of resin layers 211...21N. The resin layer 21N can be used as a resin layer, a pressure-sensitive adhesive layer, an adhesive layer, or the like.
[0036] (Resin layer) The resin layers included in the multilayer resin layer 20 can be made of any appropriate resin depending on the application of the glass resin composite 1. Examples of resins forming the resin layers include polyvinyl alcohol (PVA)-based resins, polyolefin-based resins, cyclic olefin-based resins, polycarbonate-based resins, cellulose-based resins, polyester-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, (meth)acrylic resins, (meth)acrylic urethane-based resins, polysulfone-based resins, acetate-based resins, epoxy-based resins, silicone-based resins, polyarylate-based resins, polysulfone-based resins, polyetherimide-based resins, epoxy-based resins, urethane-based resins, and silicone-based resins.
[0037] The thickness of the resin layer is not particularly limited, and may be any appropriate thickness depending on the application, type, etc.
[0038] The resin layer can be used as an optical film, a conductive film, a light control film, etc. Examples of optical films include a polarizing plate, a retardation plate, and an isotropic film.
[0039] ((Polarizing plate)) The case where the resin layer is used as a polarizing plate will be described.
[0040] The polarizing plate has a film-like polarizer.
[0041] The thickness of the polarizer is not particularly limited and may be set appropriately depending on the purpose. The thickness of the polarizer may be, for example, 1 μm to 80 μm.
[0042] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more. The degree of polarization of the polarizer is preferably 99.8% or more.
[0043] The polarizer is preferably an iodine-based polarizer, which can be made of a polyvinyl alcohol-based resin (PVA-based resin) containing iodine.
[0044] Any suitable resin can be used as the PVA-based resin. Examples of the PVA-based resin include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA-based resin is usually 85 mol% to 100 mol%. The saponification degree can be determined in accordance with JIS K6726-1994. By using a PVA-based resin having such a saponification degree, a polarizer having excellent durability can be obtained.
[0045] The average degree of polymerization of the PVA resin may be appropriately selected depending on the purpose, and is usually from 1000 to 10000. The average degree of polymerization can be determined in accordance with JIS K 6726:1994.
[0046] The polarizing plate may have a protective film on at least one surface of the polarizer. The protective film may be formed using any appropriate material, and examples of the material for forming the protective film include polyester resins such as polyethylene terephthalate (PET), cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as norbornene resins, olefin resins such as polyethylene and polypropylene, and (meth)acrylic resins.
[0047] The protective film may have ultraviolet absorbing ability. The protective film can exhibit ultraviolet absorbing ability by appropriately containing any ultraviolet absorbing agent. Examples of the ultraviolet absorbing agent include oxybenzophenone-based compounds, benzotriazole-based compounds, salicylic acid ester-based compounds, benzophenone-based compounds, cyanoacrylate-based compounds, nickel complex salt-based compounds, and triazine-based compounds. The content ratio of the ultraviolet absorbing agent may be any amount that can exhibit sufficient ultraviolet absorbing ability, and is, for example, preferably 0.01 parts by mass to 30 parts by mass with respect to 100 parts by mass of the protective film.
[0048] The protective film can be formed by a general film-forming method, such as a melt extrusion method, a solution casting method, a calendar method, or a compression molding method.
[0049] The polarizer and the protective film are laminated via any suitable adhesive layer.
[0050] The thickness of the protective film is not particularly limited and may be, for example, 5 μm to 55 μm.
[0051] (Adhesive layer) The adhesive layer included in the multilayer resin layer 20 can be formed by using any appropriate adhesive. Examples of the adhesive include a rubber-based adhesive, an acrylic-based adhesive, a silicone-based adhesive, a urethane-based adhesive, a vinyl alkyl ether-based adhesive, a polyvinyl alcohol-based adhesive, a polyvinyl pyrrolidone-based adhesive, a polyacrylamide-based adhesive, and a cellulose-based adhesive.
[0052] The adhesive is preferably an acrylic adhesive. The acrylic adhesive contains a (meth)acrylic polymer as a base polymer. The content of the (meth)acrylic polymer in the acrylic adhesive is preferably 50 parts by mass or more per 100 parts by mass of the total solid content in the acrylic adhesive.
[0053] The (meth)acrylic polymer contains a structural unit derived from an alkyl (meth)acrylate. Examples of the alkyl (meth)acrylate include acrylates having a linear or branched alkyl group with 1 to 18 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, an amyl group, a hexyl group, a cyclohexyl group, a heptyl group, a 2-ethylhexyl group, an isooctyl group, a nonyl group, a decyl group, an isodecyl group, a dodecyl group, an isomyristyl group, a lauryl group, a tridecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, and an octadecyl group. These can be used alone or in combination. The average carbon number of these alkyl groups is preferably 3 to 9.
[0054] The content of the structural unit derived from alkyl (meth)acrylate is preferably 70 parts by mass or more based on 100 parts by mass of the (meth)acrylic polymer.
[0055] The (meth)acrylic polymer may further contain structural units derived from other monomers such as carboxyl group-containing monomers, hydroxyl group-containing monomers, amide group-containing monomers, and aromatic ring-containing (meth)acrylates. When the adhesive contains a crosslinking agent, the carboxyl group-containing monomers, hydroxyl group-containing monomers, amide group-containing monomers, and aromatic ring-containing (meth)acrylates become reaction sites with the crosslinking agent. In particular, the carboxyl group-containing monomers and hydroxyl group-containing monomers are highly reactive with the intermolecular crosslinking agent, and are therefore preferably used to improve the cohesiveness and heat resistance of the adhesive layer. In addition, as the other monomers, copolymerization monomers having a functional group containing an unsaturated double bond such as a (meth)acryloyl group or a vinyl group may be used.
[0056] The carboxyl group-containing monomer is a compound that contains a carboxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group, a vinyl group, etc. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid.
[0057] The content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer. Within this range, the glass resin composite 1 can exhibit excellent durability and reworkability.
[0058] The hydroxyl group-containing monomer is a compound that contains a hydroxyl group in its structure and a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Specific examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate. Among the above hydroxyl group-containing monomers, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the viewpoint of durability, and 4-hydroxybutyl (meth)acrylate is more preferred.
[0059] The content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.01 to 3 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer. Within this range, the glass resin composite 1 can exhibit excellent durability and adhesive properties.
[0060] The amide group-containing monomer is a compound that contains an amide group in its structure and also contains a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of the amide group-containing monomer include acrylamide-based monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylol-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl group-containing lactam-based monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam.
[0061] The content of the structural unit derived from the amide group-containing monomer is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer. Within this range, the glass resin composite 1 can exhibit excellent durability and adhesive properties.
[0062] The aromatic ring-containing (meth)acrylate is a compound that contains an aromatic ring structure in its structure and also contains a (meth)acryloyl group. Examples of the aromatic ring include a benzene ring, a naphthalene ring, and a biphenyl ring. Specific examples of the aromatic ring-containing (meth)acrylate include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxyethyl ... Examples of the acrylates include those having a benzene ring, such as methoxy-3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, cresyl (meth)acrylate, and polystyryl (meth)acrylate; those having a naphthalene ring, such as hydroxyethylated β-naphthol acrylate, 2-naphthoethyl (meth)acrylate, 2-naphthoxyethyl acrylate, and 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate; and those having a biphenyl ring, such as biphenyl (meth)acrylate.
[0063] The content of the structural unit derived from the aromatic ring-containing (meth)acrylate is preferably 25 parts by mass or less based on 100 parts by mass of the (meth)acrylic polymer. If it is within such a range, the glass resin composite 1 can exhibit excellent durability.
[0064] The weight-average molecular weight (Mw) of the (meth)acrylic polymer is preferably 1,000,000 to 2,500,000. Within this range, the glass resin composite 1 can exhibit excellent durability and heat resistance. The weight-average molecular weight is measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene.
[0065] The (meth)acrylic polymer can be obtained by polymerization using a general polymerization method.
[0066] The adhesive may further contain a silane coupling agent. By using an adhesive containing a silane coupling agent, an adhesive layer having excellent durability can be formed. As the silane coupling agent, a silane coupling agent having any appropriate functional group can be used. Examples of the functional group include a vinyl group, an epoxy group, an amino group, a mercapto group, a (meth)acryloxy group, an acetoacetyl group, an isocyanate group, a styryl group, and a polysulfide group. Specific examples of the silane coupling agent include vinyl group-containing silane coupling agents such as vinyltriethoxysilane, vinyltripoxysilane, vinyltriisopropoxysilane, and vinyltributoxysilane; epoxy group-containing silane coupling agents such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, and γ-triethoxysilyl-N- Examples of the silane coupling agents include amino group-containing silane coupling agents such as (1,3-dimethylbutylidene)propylamine and N-phenyl-γ-aminopropyltrimethoxysilane; mercapto group-containing silane coupling agents such as γ-mercaptopropylmethyldimethoxysilane; styryl group-containing silane coupling agents such as p-styryltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as γ-acryloxypropyltrimethoxysilane and γ-methacryloxypropyltriethoxysilane; isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane; and polysulfide group-containing silane coupling agents such as bis(triethoxysilylpropyl)tetrasulfide.
[0067] Silane coupling agents having multiple alkoxysilyl groups in the molecule may be used as the silane coupling agent. Examples of such silane coupling agents include X-41-1053, X-41-1059A, X-41-1056, X-41-1805, X-41-1818, X-41-1810, and X-40-2651 manufactured by Shin-Etsu Chemical Co., Ltd.
[0068] The content of the silane coupling agent is preferably 0.001 to 5 parts by mass relative to 100 parts by mass of the base polymer in the pressure-sensitive adhesive.
[0069] As the silane coupling agent, a thiol group-containing silane coupling agent may be used. By using a thiol group-containing silane coupling agent, a pressure-sensitive adhesive layer having excellent durability and reworkability can be formed.
[0070] As the thiol group-containing silane coupling agent, an oligomer-type thiol group-containing silane coupling agent is used. By using an oligomer-type thiol group-containing silane coupling agent, a pressure-sensitive adhesive layer having excellent durability and reworkability can be formed. Here, the oligomer type refers to a polymer of a dimer or more and less than 100 monomers, and the weight average molecular weight (Mw) of the oligomer-type silane coupling agent is preferably 300 to 30,000. As the oligomer-type thiol group-containing silane coupling agent, an oligomer-type thiol group-containing silane coupling agent having two or more alkoxysilyl groups in the molecule is preferable. As such a silane coupling agent, for example, X-41-1805, X-41-1810, X-41-1818, etc. manufactured by Shin-Etsu Chemical Co., Ltd. can be mentioned.
[0071] The number of alkoxysilyl groups in the thiol group-containing silane coupling agent is not particularly limited, but it is preferable that there are two or more alkoxysilyl groups in the molecule.
[0072] The content of the alkoxy group in the thiol group-containing silane coupling agent is preferably 10% by mass to 60% by mass in the silane coupling agent.
[0073] The type of alkoxy group is not particularly limited, but examples thereof include alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, propoxy, butoxy, pentyloxy, and hexyloxy. Among these, methoxy and ethoxy are preferred, and methoxy is more preferred. It is preferred that both methoxy and ethoxy are contained in one molecule.
[0074] The thiol equivalent (mercapto equivalent) of the thiol group-containing silane coupling agent is preferably 200 g / mol to 1000 g / mol or less.
[0075] The adhesive may further include a crosslinking agent. As the crosslinking agent, an organic crosslinking agent or a polyfunctional metal chelate can be used. As the organic crosslinking agent, an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, an imine crosslinking agent, etc. can be mentioned. In the polyfunctional metal chelate, a polyvalent metal is covalently bonded or coordinately bonded to an organic compound. As the crosslinking agent, at least one of an isocyanate crosslinking agent and a peroxide crosslinking agent is preferable, and it is more preferable to use an isocyanate crosslinking agent and a peroxide crosslinking agent in combination.
[0076] As the isocyanate-based crosslinking agent, a compound having at least two isocyanate groups can be used. For example, the isocyanate-based crosslinking agent may be an aliphatic diisocyanate, an alicyclic diisocyanate, an aromatic diisocyanate, or the like, which is generally used in a urethane reaction.
[0077] Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0078] Examples of alicyclic diisocyanates include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0079] Examples of aromatic diisocyanates include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0080] Examples of the isocyanate-based crosslinking agent include polymers (dimers, trimers, pentamers, etc.) of diisocyanates such as the above-mentioned aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates, and urethane-modified products, urea-modified products, biuret-modified products, alphanate-modified products, isocyanurate-modified products, and carbodiimide-modified products obtained by reacting the diisocyanates with polyhydric alcohols such as trimethylolpropane.
[0081] Commercially available isocyanate crosslinking agents include, for example, products manufactured by Nippon Polyurethane Industry Co., Ltd. under the trade names "Millionate MT", "Millionate MTL", "Millionate MR-200", "Millionate MR-400", "Coronate L", "Coronate HL", and "Coronate HX", products manufactured by Mitsui Chemicals Co., Ltd. under the trade names "Takenate D-110N", "Takenate D-120N", "Takenate D-140N", "Takenate D-160N", "Takenate D-165N", "Takenate D-170HN", "Takenate D-178N", "Takenate 500", and "Takenate 600". These compounds may be used alone or in combination of two or more.
[0082] As the isocyanate-based crosslinking agent, aliphatic polyisocyanate and its modified aliphatic polyisocyanate-based compound are preferred. By using the aliphatic polyisocyanate-based compound, the crosslinked structure is highly flexible, and the stress caused by the expansion / contraction of the adhesive layer is easily alleviated, so that the adhesive layer can be formed with excellent durability and adhesive properties. As the aliphatic polyisocyanate-based compound, hexamethylene diisocyanate or its modified product is particularly preferred.
[0083] As the peroxide-based crosslinking agent, it is preferable to use a peroxide having a 1-minute half-life temperature of 80° C. to 160° C. Examples of the peroxide-based crosslinking agent include di(2-ethylhexyl)peroxydicarbonate (1-minute half-life temperature: 90.6° C.), di(4-t-butylcyclohexyl)peroxydicarbonate (1-minute half-life temperature: 92.1° C.), di-sec-butylperoxydicarbonate (1-minute half-life temperature: 92.4° C.), t-butylperoxyneodecanoate (1-minute half-life temperature: 103.5° C.), t-hexylperoxypivalate (1-minute half-life temperature: 109.1° C.), t-butylperoxypivalate (1-minute half-life temperature: 110.3° C.), dilauroyl peroxide, (1-minute half-life temperature: 116.4°C), di-n-octanoyl peroxide (1-minute half-life temperature: 117.4°C), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (1-minute half-life temperature: 124.3°C), di(4-methylbenzoyl)peroxide (1-minute half-life temperature: 128.2°C), dibenzoyl peroxide (1-minute half-life temperature: 130.0°C), t-butylperoxyisobutyrate (1-minute half-life temperature: 136.1°C), 1,1-di(t-hexylperoxy)cyclohexane (1-minute half-life temperature: 149.2°C), and the like. Among these, di(4-t-butylcyclohexyl) peroxydicarbonate (1-minute half-life temperature: 92.1°C), dilauroyl peroxide (1-minute half-life temperature: 116.4°C), dibenzoyl peroxide (1-minute half-life temperature: 130.0°C), etc. are preferably used because of their excellent crosslinking reaction efficiency. The half-life of a peroxide is an index showing the decomposition speed of the peroxide, and refers to the time until the remaining amount of the peroxide is reduced to half. The decomposition temperature for obtaining the half-life at any time and the half-life time at any temperature are described in the manufacturer's catalog, for example, in "Organic Peroxide Catalog 9th Edition (May 2003)" manufactured by NOF Corporation.
[0084] The content of the crosslinking agent is preferably 0.01 to 3 parts by mass relative to 100 parts by mass of the base polymer. Within this range, a pressure-sensitive adhesive layer having suitable creep characteristics, elastic modulus, etc. can be formed.
[0085] The adhesive may further contain any suitable ionic compound. As the ionic compound, for example, (perfluoroalkylsulfonyl)imide lithium salt, bis(trifluoromethanesulfonylimide)lithium, etc. are used. The content of the ionic compound is preferably 10 parts by mass or less with respect to 100 parts by mass of the base polymer.
[0086] The pressure-sensitive adhesive layer may further contain any other suitable additives, such as polyether compounds of polyalkylene glycols such as polypropylene glycol, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, and foils.
[0087] The thickness of the pressure-sensitive adhesive layer is not particularly limited and may be, for example, 10 μm to 200 μm.
[0088] (adhesive layer) The adhesive layer included in the multi-layer resin layer 20 can be formed using any suitable adhesive. As the adhesive, a photocurable or thermosetting adhesive is used. As the adhesive, for example, an epoxy adhesive, a rubber adhesive, an acrylic adhesive, a silicone adhesive, a urethane adhesive, a mixture thereof, etc. can be used. As adhesive materials that can be used for the adhesive, a mixture of polyurethane, polyvinyl chloride, polyvinyl acetate, vinyl alcohol, etc.; an epoxy resin, polyvinyl butyral, polymethacrylic acid ester, cyclized rubber, ethyl cellulose, vinyl copolymer, etc. can be used. Epoxy resin, polyvinyl butyral, polymethacrylic acid ester, cyclized rubber, ethyl cellulose, vinyl copolymer are preferable because they have good adhesion to the glass sheet 10.
[0089] The adhesive layer is preferably optically transparent in the visible wavelength range. The adhesive layer may be formed by curing the adhesive with light, heat, or a combination of these.
[0090] The thickness of the adhesive layer is not particularly limited and may be, for example, 1 μm to 50 μm.
[0091] (Transparent conductive layer) The multilayer resin layer 20 may have a transparent conductive layer. Examples of the transparent conductive layer include a metal oxide layer, a metal layer, a layer containing a conductive polymer, a layer containing metal nanowires, and a layer composed of a metal mesh.
[0092] [Protective layer] The glass resin composite 1 may be temporarily provided with a protective layer on the surface of the glass sheet 10 opposite to the multilayer resin layer 20. The protective film temporarily protects the surface of the glass sheet 10 and prevents contamination of the surface by foreign matter or the like.
[0093] Examples of materials that can be used to form the protective film include polyethylene, polyvinyl chloride, polyethylene terephthalate, polyvinylidene chloride, polypropylene, polyvinyl alcohol, polyester, polycarbonate, polystyrene, polyacrylonitrile, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-methacrylic acid copolymer, nylon, cellophane, and silicone resin.
[0094] The thickness of the protective layer is not particularly limited, but may be, for example, 100 μm or less.
[0095] The glass resin composite 1 may optionally include a functional layer, such as a transparent electrode, an anti-reflection layer, or an anti-fouling layer, on the surface of the glass sheet 10 opposite to the multilayer resin layer 20. The thickness of the functional layer is not particularly limited, but may be, for example, 1 μm or less.
[0096] <Method of manufacturing glass resin composite> (Formation of Laminate) A roll-to-roll process is used to laminate the glass sheet 10 and the multi-layer resin layer 20 to form a laminate.
[0097] The length of the glass sheet 10 before cutting is a long glass ribbon. Therefore, the length of the glass sheet 10 before cutting is, for example, preferably 50 m or more, more preferably 100 m or more, and further preferably 500 m or more. The upper limit of the length of the glass sheet 10 before cutting is not particularly limited, and may be, for example, 1000 m.
[0098] When the multilayer resin layer 20 includes an adhesive layer as a resin layer, the laminate can be formed by laminating the remaining resin layers of the multilayer resin layer 20 to the glass sheet 10 via the adhesive layer, which is one of the resin layers of the multilayer resin layer 20.
[0099] The laminate can also be formed by applying a resin solution for forming a resin layer to one main surface of the glass sheet 10 or to a main surface of one of the resin layers of the multilayer resin layer 20 that is different from the glass sheet 10 side to form a resin layer.
[0100] Examples of methods for applying the resin solution used to form the resin layer include coating methods such as air doctor coating, blade coating, knife coating, reverse coating, transfer roll coating, gravure roll coating, kiss coating, cast coating, spray coating, slot orifice coating, calendar coating, electrodeposition coating, dip coating, and die coating; and printing methods such as letterpress printing methods such as flexographic printing, intaglio printing methods such as direct gravure printing and offset gravure printing, lithographic printing methods such as offset printing, and stencil printing methods such as screen printing.
[0101] When one of the resin layers constituting the multi-layer resin layer 20 is a curable resin layer such as an adhesive layer, the resin solution constituting the resin layer may be cured by using any appropriate curing method according to the type of the resin layer. Examples of the curing method include a method of curing the resin solution by ultraviolet irradiation or heat treatment.
[0102] (Cutting the laminate) Next, the laminate formed by laminating the glass sheet 10 and the multilayer resin layer 20 is cut to a predetermined size to obtain a glass resin composite 1. For example, as shown in Fig. 2, the obtained multiple glass resin composites 1 are attached to one main surface of a rolled flexible film substrate 101 at predetermined intervals by a nip mechanism 120 via an adhesive or the like while being transported from a pay-out roller 110 using a roll-to-roll transport device 100, and then wound into a roll by a wind-up roller 130.
[0103] The laminate may be cut by any suitable method, for example, by mechanically cutting the laminate, by providing a scratch (scribe) on the surface of the laminate and then growing (breaking) a crack by heat or bending stress, by irradiating a laser beam to divide the laminate, or by using a full back, water jet, or end mill to divide the laminate.
[0104] The laminate may be cut into individual glass sheets 10 or individual multilayer resin layers 20 using any of the cutting methods described above.
[0105] Of the above-mentioned cutting methods, the method of cutting the laminate by irradiating laser light to divide the laminate is preferred from the standpoint of ease of cutting the laminate and ease of adjusting the Young's modulus of at least one of the glass sheet 10 and the multilayer resin layer 20 of the laminate.
[0106] A method of dividing a laminate by irradiating with laser light will be described. When using a method of dividing a laminate by irradiating with laser light, the laminate may be divided using a laser light irradiating device that appropriately irradiates any laser light.
[0107] The laminate is placed on the stage of a laser beam irradiation device. The stage is movably arranged in the laser beam irradiation device, and the laser light source is fixedly arranged. The laser beam irradiation device moves the stage to move the position of the laser beam irradiated onto the laminate.
[0108] Examples of laser light include gas lasers such as CO2 lasers and excimer lasers; solid-state lasers such as YAG lasers; semiconductor lasers; and ultrashort pulse lasers.
[0109] The laminate may be cut by forming a processing mark along the planned cutting line on the laminate with a laser beam. The processing mark may be provided in the form of a perforation along the planned cutting line, or may be provided as a continuous line. The processing mark may be a through hole penetrating each layer, or may be a non-through hole.
[0110] It is preferable to use different laser beams for irradiating the surface of the multilayer resin layer 20 and the surface of the glass sheet 10. That is, it is preferable to irradiate the surfaces of the glass sheet 10 and the multilayer resin layer 20 with different laser beams to divide the laminate. In each of the steps of irradiating the surface of the glass sheet 10 with a laser and irradiating the surface of the multilayer resin layer 20 with a laser beam, the laser beam can be used to leave processing marks on each layer, making it easier to cut the laminate.
[0111] An ultrashort pulse laser is preferably used as the laser light irradiated onto the surface of the glass sheet 10. The wavelength of the ultrashort pulse laser emitted from the ultrashort pulse laser device is preferably 500 nm to 2500 nm. The pulse width of the ultrashort pulse laser is preferably 100 picoseconds or less, more preferably 50 picoseconds or less. The oscillation form of the ultrashort pulse laser may be single pulse oscillation or may be multi-pulse oscillation in a birth mode.
[0112] Examples of the laser light irradiated to the surface of the multilayer resin layer 20 include CO2 laser, CO laser, visible light pulse laser, and ultraviolet light pulse laser. Examples of the visible light pulse laser and ultraviolet light pulse laser include a laser with an oscillating laser light wavelength of 532 nm, 355 nm, 349 nm, or 266 nm (high-order harmonics of a solid-state laser light source using Nd:YAG, Nd:YLF, or YVO4 as a medium), an excimer laser with an oscillating laser light wavelength of 351 nm, 248 nm, 222 nm, 193 nm, or 157 nm, and an F2 laser with an oscillating laser light wavelength of 157 nm. In addition, as the laser light, a pulse laser with an oscillating laser light wavelength outside the ultraviolet range and a pulse width on the order of femtoseconds or picoseconds may be used. The oscillation form of the laser light irradiated to the multilayer resin layer 20 may be pulse oscillation or continuous oscillation. The spatial intensity distribution of the laser light may be a Gaussian distribution or a flat-top distribution.
[0113] The spot diameter at the irradiation position of the laser light on the multilayer resin layer 20 may be set appropriately, and may be, for example, 300 μm or less.
[0114] The stage movement speed during irradiation of the laminate with the laser light may be set arbitrarily as appropriate. The stage movement speed corresponds to the relative movement speed of the laser light with respect to the laminate, and by changing the stage movement speed, different energies can be applied to the laminate.
[0115] When different laser beams are irradiated onto the surfaces of the glass sheet 10 and the multilayer resin layer 20, the stage movement speed may be different when irradiating the glass sheet 10 with the laser beam and when irradiating the glass sheet 10 of the laminate with the laser beam.
[0116] When an ultrashort pulse laser is irradiated onto the surface of the glass sheet 10 as laser light, the stage movement speed can be adjusted to make it easier to cut the laminate while preventing damage to the glass sheet 10, such as cracks.
[0117] When the surface of the multilayer resin layer 20 is irradiated with a CO2 laser as the laser light, the degree to which the multilayer resin layer 20 is thermally deteriorated by the CO2 laser can be adjusted by adjusting the stage movement speed. When the multilayer resin layer 20 is thermally deteriorated by the CO2 laser, the flexibility of the multilayer resin layer 20 tends to decrease and the Young's modulus tends to decrease. The higher the stage movement speed during the CO2 laser irradiation, the more the multilayer resin layer 20 is prevented from being thermally deteriorated by the CO2 laser, so that the multilayer resin layer 20 maintains its flexibility and the decrease in the Young's modulus of the multilayer resin layer 20 is suppressed. On the other hand, the lower the stage movement speed during the CO2 laser irradiation, the more likely the multilayer resin layer 20 is to be thermally deteriorated by the CO2 laser, so that the flexibility of the multilayer resin layer 20 decreases and the Young's modulus of the multilayer resin layer 20 decreases.
[0118] When different laser beams are irradiated onto the surfaces of the glass sheet 10 and the multilayer resin layer 20, the glass sheet 10 is cut using an ultrashort pulse laser, which can prevent damage such as cracks from being caused to the glass sheet 10 and facilitate cutting the laminate. For the multilayer resin layer 20, a CO2 laser or the like can be used to prevent thermal deterioration of the multilayer resin layer 20. Therefore, by irradiating the multilayer resin layer 20 with a CO2 laser as the laser beam and then irradiating the glass sheet 10 with an ultrashort pulse laser beam as the laser beam, the laminate can be cut while more effectively preventing thermal deterioration of the multilayer resin layer 20.
[0119] When the processing marks (through holes or through-holes) are provided in the form of perforations, the pitch of the processing marks is preferably 10 μm or less, and more preferably 5 μm or less. Within such a range, the laminate can be divided satisfactorily.
[0120] After irradiation with the laser light, the laminate may be divided by, for example, applying an external force to fold the laminate, heating the area near the processing marks with infrared light, applying vibrations with an ultrasonic roller, or adsorbing a part of the laminate to a suction cup and lifting it up.
[0121] As described above, by cutting the laminate, a plurality of glass resin composites 1 are obtained. As described above, the obtained plurality of glass resin composites 1 can be attached at predetermined intervals to one main surface of a film substrate via an adhesive or the like by a roll-to-roll process and wound into a roll.
[0122] In this way, the glass resin composite 1 includes the glass sheet 10 and the multilayer resin layer 20 composed of one or more resin layers 21N. When the thickness of the glass resin composite is 800 μm or less and the glass resin composite 1 is bent toward its lower surface 1a with a curvature radius satisfying the above formula (1), the probability of cracks occurring in the glass sheet 10 can be 10% or less. The elastic modulus and thickness of the multilayer resin layer 20 are the sum of the elastic modulus and thickness of all the resin layers 21N constituting the multilayer resin layer 20. If the relationship between the elastic modulus and thickness of all the resin layers 21N constituting the multilayer resin layer 20 is equal to or less than a value satisfying the above formula (1), the glass sheet 10 can have high bending durability. Therefore, even if a crack occurs on the end surface of the glass sheet 10 when the relationship between the elastic modulus and thickness of the resin layers 21N constituting the multilayer resin layer 20 is equal to or less than a value satisfying the above formula (1) and the glass resin composite 1 is bent so that the glass sheet 10 side is convex, the progression of the crack can be suppressed and the occurrence of a crack in the effective area of the surface can be suppressed. Therefore, if the glass resin composite 1 is bent with a radius of curvature equal to or less than the value that satisfies the above formula (1) so that the glass sheet 10 side is convex, the occurrence of cracks in the effective area of the surface of the glass sheet 10 can be suppressed even when a roll-to-roll process is used.
[0123] The effective area is the area in the glass resin composite 1 where the glass sheet 10 is finally used or where it is planned to be put to practical use later. The effective area is the remaining area excluding the area within 1 / 6 of the outer periphery of the surface of the glass sheet 10 from the outer periphery of the surface, preferably the remaining area excluding the area within 1 / 10 of the outer periphery of the surface, and more preferably the remaining area excluding the area within 1 / 15 of the outer periphery of the surface. For example, when one side of the outer periphery of the surface of the glass sheet 10 is 300 mm, the effective area is the remaining area excluding the area within 50 mm from the outer periphery of 300 mm.
[0124] When the glass resin composite 1 is bent toward its upper surface 1b with a radius of curvature that satisfies the above formula (1), the probability of cracks occurring in the glass sheet 10 can be 10% or less. As described above, if the relationship between the elastic modulus and thickness of the resin layer 21N is equal to or less than the value that satisfies the above formula (1), the glass sheet 10 can have improved bending durability. Therefore, even if a crack occurs on the end surface of the glass sheet 10 when the relationship between the elastic modulus and thickness of the resin layer 21N constituting the multilayer resin layer 20 is equal to or less than the value that satisfies the above formula (1) and the glass resin composite 1 is bent so that the multilayer resin layer 20 side is convex, the progression of the crack can be suppressed and the crack can be suppressed from occurring in the effective area of the surface. Therefore, even if the glass resin composite 1 is bent with a radius of curvature that is equal to or less than the value that satisfies the above formula (1) so that the multilayer resin layer 20 side is convex, the glass resin composite 1 can be suppressed from occurring in the effective area of the surface of the glass sheet 10 when using a roll-to-roll process.
[0125] In the glass resin composite 1, the thickness of the glass sheet 10 can be set to 20% to 75% of the thickness of the glass resin composite 1. This makes it easier to set the configuration of each resin layer 21N of the multilayer resin layer 20 so that the relationship between the elastic modulus and thickness of the resin layer 21N is equal to or smaller than the value that satisfies the above formula (1). Therefore, even if the glass resin composite 1 is bent to a value that satisfies the above formula (1), it is possible to suppress the occurrence of cracks in the effective area of the surface of the glass sheet 10.
[0126] In the glass resin composite 1, the thickness of the glass sheet 10 can be set to 30 μm to 300 μm. This makes it easier to set the configuration of each resin layer 21N of the multilayer resin layer 20 so that the relationship between the elastic modulus and thickness of the resin layer 21N is equal to or smaller than the value that satisfies the above formula (1). Therefore, even if the glass resin composite 1 is bent to a value that satisfies the above formula (1), it is possible to suppress the occurrence of cracks in the effective area of the surface of the glass sheet 10.
[0127] As described above, even when the glass resin composite 1 is transported and rolled up in a roll-to-roll process, the occurrence of cracks in the effective area of the surface of the glass sheet 10 can be suppressed, and therefore the glass resin composite 1 can be effectively used in image display devices such as liquid crystal display elements and organic EL elements, semiconductor elements, solar cells, etc.
[0128] In this embodiment, the glass resin composite 1 may have a multilayer resin layer 20 on the upper surface of the glass sheet 10, as shown in Figure 3, or may have a multilayer resin layer 20 on both the lower surface 10a and the upper surface 10b of the glass sheet 10, as shown in Figure 4.
[0129] Although the embodiment has been described above, the above embodiment is presented as an example, and the present invention is not limited to the above embodiment. The above embodiment can be implemented in various other forms, and various combinations, omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. EXAMPLES
[0130] The embodiments will be described in more detail below with reference to examples and comparative examples, but the embodiments are not limited to these examples and comparative examples.
[0131] <Preparation of glass-resin composite> [Example 1] (Preparation of Laminate) An adhesive (epoxy resin (Celloxide 2021P, Daicel Chemical Industries, Ltd., thickness: 10 μm)) was applied to one main surface of a 300 mm square glass sheet (Nippon Electric Glass Co., Ltd., "OA-10", thickness: 100 μm), and a PET layer (A4360, Toyobo Co., Ltd., thickness: 100 μm) was laminated on top of it. After that, ultraviolet light (wavelength: 365 nm, intensity: 1000 mJ / cm) was applied from a high-pressure mercury lamp. 2The adhesive was cured by irradiating the above-mentioned light to the adhesive, thereby producing a laminate 1 in which a multilayer resin layer 1 made of an adhesive layer and a PET layer was laminated on a glass sheet.
[0132] (Removal of multiple resin layers) The laminate 1 was placed on a stage with the adhesive layer side facing up, and a CO2 laser device (250 kHz, output 10 W) was used to focus a CO2 laser emitted from a CO2 laser light source using a focusing lens to a spot diameter of 100 μm, and irradiated onto the multilayer resin layer 1. The stage movement speed was set to 350 mm / s, which was the relative movement speed (processing speed) of the CO2 laser with respect to the laminate 1, and the multilayer resin layer 1 was irradiated with the CO2 laser so that the in-plane dimensions of the laminate became 300 mm × 300 mm, removing the multilayer resin layer 1 and half-cutting the laminate 1.
[0133] The stage movement speed during CO2 laser irradiation corresponds to the relative movement speed of the CO2 laser with respect to the glass sheet and the multilayer resin layer 1, and indicates the degree to which the glass sheet and the multilayer resin layer 1 are thermally deteriorated by the CO2 laser, and therefore the flexibility of the glass sheet and the multilayer resin layer 1 tends to decrease and the Young's modulus tends to decrease. By increasing the stage movement speed during CO2 laser irradiation, the thermal deterioration of the glass sheet and the multilayer resin layer 1 caused by the CO2 laser is suppressed, and the decrease in the Young's modulus of the glass sheet and the multilayer resin layer 1 is suppressed. On the other hand, by slowing down the stage movement speed during CO2 laser irradiation, the glass sheet and the multilayer resin layer 1 are more likely to be thermally deteriorated by the CO2 laser, and therefore the glass sheet and the multilayer resin layer 1 become hard and the Young's modulus of the glass sheet and the multilayer resin layer 1 decreases.
[0134] (Glass sheet removal) Next, the glass sheet was placed on the stage with the glass sheet side facing up, and an ultrashort pulse laser was irradiated from an ultrashort pulse laser light source via an optical system using an ultrashort pulse laser device (oscillation wavelength 1064 nm, ultrashort pulse laser pulse width 10 psec, pulse repetition frequency 125 kHz, pulse energy 80 uJ) to the surface of the glass sheet opposite to the resin film side. The stage movement speed was set to 125 mm / s, and the relative movement speed (processing speed) of the ultrashort pulse laser with respect to the laminate 1 was set, and the ultrashort pulse laser was scanned along the outer periphery of the adhesive layer and the resin layer, forming perforated through holes with a pitch of 1 μm as processing marks. The laminate 1 was pulled in the horizontal direction and divided into multiple pieces (4 pieces), to produce a glass resin composite test piece (composite chip).
[0135] (Calculation of radius of curvature) The radius of curvature R0 was calculated using the following formula (1).
[0136]
number
[0137] In the formula (1), 1 is 3 layers, n is 2 layers, and the Young's modulus of the resin layer was measured using an autograph under the following Young's modulus measurement conditions. -Young's modulus measurement conditions- ·Measurement temperature: 25℃ Sample size: thickness 50μm, width 2cm, length 15cm Distance between chucks: 10cm Pulling speed: 10mm / min
[0138] [Example 2] The same glass resin composite test piece as in Example 1 was used.
[0139] [Example 3] In Example 1, the multilayer resin layer 1 formed on one main surface of the glass sheet was changed to a multilayer resin layer 2 in which a triacetyl cellulose (TAC) layer (thickness: 40 μm), a polyvinyl alcohol resin (PVA) layer (thickness: 18 μm), a TAC layer (thickness: 40 μm), a pressure-sensitive adhesive (PSA) layer (thickness: 20 μm), and a PET layer (thickness: 100 μm) were laminated in this order on an adhesive (epoxy resin ("Celloxide 2021P", manufactured by Daicel Chemical Industries, Ltd., thickness: 10 μm). Except for this, the same procedure as in Example 1 was performed to prepare a glass resin composite test piece.
[0140] The PSA layer was prepared as follows. A four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler was charged with 90.7 parts by mass of butyl acrylate, 3 parts by mass of acrylic acid, 0.3 parts by mass of 2-hydroxybutyl acrylate, and 0.1 parts by mass of 2,2'-azobisisobutyronitrile as a polymerization initiator together with 100 g of ethyl acetate to prepare a mixture. Nitrogen gas was introduced while gently stirring the mixture to replace with nitrogen, and the liquid temperature in the flask was kept at around 55°C to carry out a polymerization reaction for 8 hours to prepare an acrylic polymer solution. An acrylic adhesive solution was prepared by mixing 0.2 parts by mass of an isocyanate crosslinking agent (Coronate L manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.3 parts by mass of benzoyl peroxide (Niper BMT manufactured by Nippon Oil & Fats Co., Ltd.), and 0.2 parts by mass of γ-glycidoxypropylmethoxysilane (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd.) with respect to 100 parts by mass of the solid content of the obtained acrylic polymer solution. Next, the acrylic adhesive solution was applied to one side of a silicone-treated PET film so that the thickness of the PSA layer after drying was 20 μm, and the PSA layer was formed by drying at 150 ° C. for 3 minutes.
[0141] [Example 4] In Example 1, the multilayer resin layer 1 formed on one main surface of the glass sheet was also formed on the other main surface of the glass sheet, and the multilayer resin layer 1 was laminated on both the top and bottom surfaces of the glass sheet. Each of the multilayer resin layers 1 laminated on both the top and bottom surfaces of the glass sheet was removed with a CO2 laser, and the removal of the multilayer resin layer 1 with a CO2 laser was performed twice. Except for this, the same procedure as in Example 1 was performed to prepare a glass resin composite test piece.
[0142] [Example 5] In Example 1, the multilayer resin layer 1 formed on one main surface of the glass sheet was changed to a multilayer resin layer 3 in which a PSA layer (thickness: 200 μm) and a PET layer (thickness: 150 μm) were laminated in this order, and the multilayer resin layer 3 was formed on the other main surface of the glass sheet. Except for this, the same procedure as in Example 1 was carried out to prepare a glass resin composite test piece.
[0143] [Comparative Examples 1 and 2] In Comparative Example 1, the same glass resin composite test piece as in Example 1 was used, and in Comparative Example 2, the same glass resin composite test piece as in Example 3 was used.
[0144] Table 1 shows the layer structure and total thickness of the laminate of each of the examples and comparative examples, and the stage movement speed and curvature radius R0 of the glass resin composite test piece during CO2 laser irradiation.
[0145] <Evaluation> The glass resin composite test pieces of each of the Examples and Comparative Examples were evaluated for the occurrence of cracks in the glass sheet and the feasibility of web transport (web handling).
[0146] [Evaluation of cracks in the effective area of the surface of a glass sheet] Next, a cylinder (SUS) with a radius of curvature satisfying the above formula (1) was prepared, and a glass resin composite test piece was wrapped around the cylinder to confirm whether or not cracks occurred in the effective area (250 mm x 250 mm) of the surface of the glass sheet. The test was performed using 30 glass resin composite test pieces. The crack occurrence rate in the effective area of the surface of the glass sheet of the 30 glass resin composite test pieces was calculated based on the following formula (i). The calculation results of the crack occurrence rate in the effective area of the surface of the glass sheet are shown in Table 1. Rate of crack occurrence in the effective area of the surface of the glass sheet [%] = number of glass-resin composite test pieces in which cracks occurred in the effective area of the surface of the glass sheet / 30 × 100 (i)
[0147] [Web handling possible] Using a roll-to-roll transport device equipped with a payout mechanism, a nip mechanism, and a winding mechanism, the multilayer resin layer side of the glass resin composite test piece was bonded to the surface of a PET carrier (100 μm) conveyed from the roll of the payout mechanism via an acrylic adhesive (thickness 25 μm). The PET carrier to which the glass resin composite test piece was bonded was conveyed to the roll of the winding mechanism and wound up. After winding, the glass resin composite test piece bonded to the PET carrier was taken, and it was confirmed whether or not cracks had occurred in the effective area (250 mm × 250 mm) of the surface of the glass sheet relative to the overall size (300 mm × 300 mm) of the main surface of the glass sheet of the glass resin composite test piece. The test was performed using 30 glass resin composite test pieces. The occurrence rate of cracks in the effective area of the surface of the glass sheet of the 30 glass resin composite test pieces was calculated based on the following formula (i), and the feasibility of web handling was evaluated based on the following evaluation criteria. The evaluation results of the feasibility of web handling are shown in Table 1. Rate of crack occurrence in the effective area of the surface of the glass sheet [%] = number of glass-resin composite test pieces in which cracks occurred in the effective area of the surface of the glass sheet / 30 × 100 (i) (judgment criteria) A: The percentage of glass resin composite test pieces in which cracks have occurred in the effective area of the surface of the glass sheet is 10% or less. B: The percentage of glass resin composite test pieces in which cracks occurred in the effective area of the surface of the glass sheet was more than 10%.
[0148] [Table 1]
[0149] As shown in Table 1, in each of the examples, the crack occurrence rate in the effective area of the surface of the glass sheet was 10% or less, and the web handling was good. On the other hand, in each of the comparative examples, the crack occurrence rate in the effective area of the surface of the glass sheet was 20% or more, and the web handling was poor.
[0150] Therefore, as long as the glass resin composite according to this embodiment satisfies the above formula (1), even if the glass sheet is transported and wound up in a roll-to-roll process, the occurrence of cracks can be suppressed in the effective area of the surface of the glass sheet, and therefore the glass resin composite can be effectively used in the roll-to-roll process.
[0151] The aspects of the embodiment of the present invention are as follows, for example. <1> A glass resin composite having one or more resin layers on at least one surface of a glass sheet, The thickness of the glass resin composite is 800 μm or less, The glass resin composite has a probability of 10% or less when the glass resin composite is bent toward one surface of the glass resin composite with a curvature radius that satisfies the following formula (1):
number
[0152] 1 Glass-resin composite 1a, 10a bottom side 1b, 10b top surface 10 Glass Sheet 20 Multilayer resin layer 211, 21N resin layer
Claims
1. A glass resin composite having one or more resin layers on at least one surface of a glass sheet, The thickness of the glass resin composite is 800 μm or less, The glass resin composite has a probability of cracking occurring in the glass sheet of 10% or less when the glass resin composite is bent toward one surface of the glass resin composite with a curvature radius that satisfies the following formula (1): [0010] (In formula (1), R 0 is the inner radius of curvature [mm] of the glass resin composite, i and k are integers, l is the number of layers [layers] including the resin layer and the glass sheet when counting from the inside of the resin glass laminate to the glass sheet, n is the total number of layers [layers], E i is the Young's modulus [MPa] of the i-th layer, and t i is the thickness [μm] of the i-th resin layer, and t 0 is 0.)
2. 2. The glass resin composite according to claim 1, wherein when the glass resin composite is bent toward the other surface of the glass resin composite with a radius of curvature that satisfies the following formula (1), the probability of cracking occurring in the glass sheet is 10% or less.
3. 2. The glass resin composite according to claim 1, wherein the thickness of the glass sheet is 20% to 75% of the thickness of the glass resin composite.
4. 2. The glass resin composite according to claim 1, wherein the glass sheet has a thickness of 30 μm to 300 μm.
5. The glass resin composite according to claim 1 , wherein the radius of curvature is a radius of a roll with which the glass resin composite comes into contact.
Citation Information
Patent Citations
Electronic devices with flexible glass polarizers
US8525405B2